The Dynamic Interaction of Second Language Motivation and Emotional Experience: The Case of Chinese Learners of English - Tian, Lixian; McCafferty, Steven G. (Frontiers in Psychology, 2022)
This study investigated the dynamic interaction of second language motivation and emotional experience for Chinese learners of English in four different contexts: 1) those in China with little or no intention of learning the language for communicative purposes; 2) those in China intending to study abroad; 3) those studying abroad in the U.S.; and 4) those who had returned to China after studying abroad. Data included interviews with representatives from different contexts and the video-recording of a narrative and descriptive task. Analysis focused on Vygotsky’s concept of perezhivanie, or how Chinese learners of English experienced their learning environments cognitively and affectively, as leading to goals and goal-directed activity across their English learning experiences. Findings showed differences among Chinese learners of English in terms of goal-directed activity and affective reaction in each of the four contexts and across members in the same contexts. The integration of individual and contextual factors constituted the plasticity of second and foreign language development and showed the diversity of individual emotional learning experience. Overall, this study emphasized how motivation shapes experience and how experience shapes motivation in the process of English learning.